Effects of Artificial Sweeteners Aspartame and Sucralose on the Size of Hepatocytes in Rat Liver - Nadia Haq, Sadia Saqib, Raafea Tafweez, Irfan Ali, Ahmad Fawad Syami (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The use of artificial sweeteners in excess these days to lose weight and to remain fit without knowing its effects on our health, gave me a thought to conduct this study to see whether they are safe or not for liver health. Objectives: The objectives of this study were to see the effects of Aspartame and Sucralose (Artificial sweeteners) on rat hepatocytes and also to compare their effects to choose relatively safe artificial sweetener for routine use. Method: 50 adult Wistar albino rats were used in this study. Animals were divided into five groups by random lottery method. Control group I animals were given distilled water by oral gavage. The group II and III animals were given 40mg and 1000mg/kg body weight of Aspartame respectively. Whereas animals of group IV and V were given 5mg and 1000mg/kg body weight of Sucralose respectively. Doses to experimental animals were given by oral gavage once daily for a total duration of eight weeks. At the end of the experiment rats were sacrificed, livers were dissected out and after specimen preservation the tissue was passed through stages of slide preparation and later H and E staining was performed. Results: Light microscopic examination of liver slides revealed that largest sizes of hepatocytes were observed in high dose groups of Aspartame and Sucralose. Conclusion: The increase in the size of hepatocytes was observed in high dose groups of Aspartame and Sucralose whereas changes seen in low dose groups were not significant. Keywords: Artificial sweeteners, Histology of rat liver, Size of hepatocytes.